Making Monolingual Corpora Comparable: a Case Study of Bulgarian and Croatian - Bekavac, Božo (Array, 2004)
This paper describes the first steps towards the creation of a Bulgarian-Croatian comparable corpus. Its base are two newspaper subcorpora from larger reference corpora of Bulgarian and Croatian. In the beginning we rely on more extralinguistically-oriented, but methodologically cleaner parameters of similarity like: specific topics, pre-defined time span and data size. The idea of ‘ light’ and ‘ hard’ comparable corpora is introduced. At this stage we aim at producing a ‘ light’ bilingual comparable corpus. The algorithm for identifying lexical similarity and aligning linguistic units is presented, and the initial experiments are outlined.